Integration of Artificial Intelligence Technology in Orthodontics: Legal and Ethical Aspects - Yessy Andriani Fauziah; Ida Bagus Narmada; Edwin R Siswantoro; Ryan Raditya (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Artificial Intelligence integration in orthodontics enhances diagnostic accuracy, treatment planning, and clinical efficiency. However, it presents legal and ethical challenges, such as liability, data privacy, and equitable access, necessitating the responsible adoption of AI in clinical practice. This literature review aims to explore the integration of AI technology in orthodontics, with a specific focus on the associated legal and ethical aspects. Review: The review aims to identify the benefits of AI in enhancing orthodontic care, examine the potential legal liabilities and regulatory considerations related to its use, and analyse the ethical implications of AI in patient data management and treatment decision-making. By providing a comprehensive overview, this study intends to highlight the importance of establishing clear guidelines and standards to ensure the safe and ethical use of AI in orthodontics. This literature review synthesizes recent research on the implementation of AI technologies in orthodontics. Studies have demonstrated that AI can process vast amounts of data quickly and accurately, thereby improving diagnostic precision and optimising treatment plans. Nonetheless, the rapid adoption of AI raises concerns about data privacy, legal liability, and equitable access to technology, which are crucial to address for the ethical integration of AI in healthcare. Conclusion: AI integration in orthodontics offers benefits like improved diagnostics and personalized treatment plans, but requires careful legal and ethical considerations.